1985
DOI: 10.1071/bt9850271
|View full text |Cite
|
Sign up to set email alerts
|

Pollination of Banksia ericifolia Smith: Birds, Mammals and Insects as Pollen Vectors

Abstract: In coastal heath, 12 km north of Sydney, Banksia ericifolia set fruit after cross-pollination but not after controlled self-pollination. Animals removed nectar and pollen from inflorescences during the day but not overnight. Introduced honeybees (Apis mellifera) and native birds (Meliphagidae, Zosteropidae) visited flowers frequently during the day, carried pollen on their body surfaces and were likely to transfer pollen between plants. Native bees, nocturnal moths and ants also visited flowers but were too in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(47 citation statements)
references
References 0 publications
2
44
0
Order By: Relevance
“…Plants that are considered to be adapted to vertebrate pollination are now increasingly visited by the invasive pollinator A. mellifera (Paton and Turner 1985;Vaughton 1992;Hansen et al 2002). Nevertheless the consequences of this phenomenon are poorly understood (Traveset and Richardson 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plants that are considered to be adapted to vertebrate pollination are now increasingly visited by the invasive pollinator A. mellifera (Paton and Turner 1985;Vaughton 1992;Hansen et al 2002). Nevertheless the consequences of this phenomenon are poorly understood (Traveset and Richardson 2006).…”
Section: Discussionmentioning
confidence: 99%
“…England et al (2001) demonstrated that for Grevillea macleayana, pollination by honeybees in a vertebrate exclusion experiment produced a small but significant decrease in outcrossing rates. Vaughton (1996) found decreased seed set (50%) in inflorescences of the same species when birds were excluded compared to inflorescences where both birds and honeybees had access, while similar vertebrate exclusion experiments by Paton and Turner (1985) and Vaughton (1992) detected no clear effect on seed production in Banksia ericifolia or Banksia spinulosa respectively. However, none of these studies comment on seed or seedling quality.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Abundance of most insects (and other arthropods) and nectar strongly fluctuate (McFarland 1985;Paton and Turner 1985;Law 1994a). Occurrence of torpor during reproduction may thus be linked to the food consumed by the mammals.…”
mentioning
confidence: 99%